A Chain Is Only As Strong as Its Weakest Link: Managing Change in the Curriculum of Industrial Management Education - Blomkvist, Pär; Uppvall, Lars (International Journal of Industrial Engineering and Management, 2012)
In this paper we discuss the process of designing a new Industrial Management Master Program given by the department of Industrial Economics and Management at Royal Institute of Technology (KTH) in Stockholm, Sweden. The foundation of the IM-master program lies in the notions of authenticity and change. We decided early on in the design process, that our aim was to teach the skills of real world change management and to “mould” our students into industrial managers able to master complex industrial change processes. But we realized that we also had to “mould” our own pedagogical tools, examination forms, and not the least, faculty, to reach our goals. These insights lead us to emphasize a Systems perspective, both in regards to program and course design and in regards to the actual management skills we wanted to teach. The objective of this paper is to present and discuss our explicit use of a systems perspective in designing the Industrial masters program. We have identified four major parts of “our system” where changes had to be made: Premises – Learning activities – Examination – Program management. These four system parts are divided into ten subsections – “systems components”. We discuss all four system parts in relation to our goals to enhance authentic skills in change management. Article history: Received (05 April 2012); Revised (15 May 2012); Accepted (25 May 2012)